Rice: Seed Systems, Production Characteristics, and Fungal Infections of Stored Grains in Major Production Zones of Liberia - Dorley, Ousman Sarlia; Ochuodho, Julius Onyango; Auma, Elmada Odeny; Were, Javan Omondi; Mutio, James Mumo (Asian Journal of Agriculture and Rural Development, 2022)
The inadequacy of information on rice farmers' situations, particularly their access to propagation materials and grain storage and the impact thereof on Liberia's food security scenario, curtails the development of strategies and interventions meant to optimize rice production. This study investigated the rice seed systems, storage methods of the harvested rice grains, and degree of fungal contamination of stored rice seeds in the major rice-producing counties of Liberia: Lofa, Bong, Montserrado, and Nimba. A mixed data collection method, comprising interviews and focus group discussions (FGDs) was adopted. Five hundred (500) farmers were purposefully selected for one-on-one interviews, and 12 FGDs were held (three in each county). The results indicated that 94.7% of farmers source seeds through informal channels. Grain for use as seed in the subsequent farming season is mainly stored in kitchen attics, a practice reported by 83.8% of the farmers, while 7.8%, 3.8%, and 4.6% of farmers stored seeds in plastic containers, nylon sacks, and jute bags, respectively. Land size was identified as the primary factor determining rice yield across the studied counties, R2 = 0.944, p = 0.001. Farmers in high-rainfall regions had a high likelihood of experiencing fungal infections on their stored grains; however, only 19.6% of farmers were aware of the health implications of consuming affected grains. Therefore, policies and support frameworks should be directed towards actualizing modern seed channels and extension services and creating awareness of the different nodes of the rice value chain.